2021
DOI: 10.1126/sciadv.abj5715
|View full text |Cite
|
Sign up to set email alerts
|

Structure of native HIV-1 cores and their interactions with IP6 and CypA

Abstract: High-resolution cryoET structures of native HIV-1 capsid in complex with IP6 and CypA are enabled by viral membrane perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 73 publications
5
30
0
Order By: Relevance
“…Imaging of single virus particles immobilized on poly-L-lysine treated glass revealed that, as expected, virions that contained G89V CA alone failed to efficiently incorporate CDR and showed marginal CDR colocalization (~2.5%) with the INmNG labeled cores. In contrast, mixed G89V/K203A CA virions efficiently incorporated CDR, showing 74 [49], we propose that as much as ~2% of virus incorporated CA is packaged in vRNPs.…”
Section: A Fraction Of Unlabeled Ca and Cdr Gets Packaged With Vrnpsmentioning
confidence: 70%
“…Imaging of single virus particles immobilized on poly-L-lysine treated glass revealed that, as expected, virions that contained G89V CA alone failed to efficiently incorporate CDR and showed marginal CDR colocalization (~2.5%) with the INmNG labeled cores. In contrast, mixed G89V/K203A CA virions efficiently incorporated CDR, showing 74 [49], we propose that as much as ~2% of virus incorporated CA is packaged in vRNPs.…”
Section: A Fraction Of Unlabeled Ca and Cdr Gets Packaged With Vrnpsmentioning
confidence: 70%
“…IP6 beads are shown as orange vdW spheres. [40, 39]. d,e Performance benchmarks with NAMD3 [38], simulating the HIV-1 conical capsid shown in panels c and d. Benchmarks were performed with one CPU per GPU employed.…”
Section: Resultsmentioning
confidence: 99%
“…After applying our framework to HIV-1 CA (Figure 1a), we assembled the full-scale conical capsid bound to the charged assembly co-factor inositol hexakisphosphate [39, 40] (Figure 1b,c, Figure S3). The complete SBCG system of the conical capsid is described by 340,000 beads, representing a larger than 200-fold reduction in particles compared to the atomistic conical capsid of the same morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retroviral Gag lattice is the most prominent feature in both mature and immature particles, and the complex arrangement of these lattices is dictated by intermolecular protein interactions located primarily within the CA domain (79)(80)(81). While the structural determinants of HIV-1 Gag oligomerization have been extensively studied in authentic particles (114)(115)(116), virus-like particles (117)(118)(119), and in vitro assemblies of purified CA proteins (120), high resolution of the structure of the HTLV-1 has been limited to nuclear magnetic resonance (NMR) studies of the HTLV-1 CA domain (121). Comparative studies probing residues within CA have identified many of the key interaction interfaces required for maintaining replication and morphology of HIV-1 (122,123), HIV-2 (124), and HTLV-1 (81), including those that dictate the formation of structural features such as the six-helix bundle of CA-SP1 and the two-and three-fold CA interfaces.…”
Section: Morphological Diversity In Human Retrovirus Particlesmentioning
confidence: 99%